Rare shocks, great recessions - Vasco Cúrdia; Marco Del Negro; Daniel L. Greenwald (Federal Reserve Bank of New York, 2012)
We estimate a DSGE model where rare large shocks can occur, but replace the commonly used Gaussian assumption with a Student's t-distribution. Results from the Smets and Wouters (2007) model estimated on the usual set of macroeconomic time series over the 1964-2011 period indicate that 1) the Student's t specification is strongly favored by the data, even when we allow for low-frequency variation in the volatility of the shocks, and 2) the estimated degrees of freedom are quite low for several shocks that drive U.S. business cycles, implying an important role for rare large shocks. This result holds even if we exclude the Great Recession from the sample. We also show that inference about low-frequency changes in volatility - and, in particular, inference about the magnitude of the Great Moderation - is different once we allow for fat tails.
Keywords: C32; E32; 330; Bayesian analysis; DSGE models; fat tails; stochastic volatility; Great Recession